(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
The study was on enhancing societal development through quality researches in Universities. The study adopted a survey research design. Purposive sampling technique was used in selecting the post graduates students, who were met in their clusters. Sixty-six (66) of them participated in the research. The instrument used was the Post-graduate Students Questionnaire (PSQ) comprising two sections: sections A and B. Section A included items soliciting responses on the categories of the postgraduate programmes, the knowledge and awareness of research ethics. The importance and the need to add it in the postgraduate curriculum were also sought. Section B of the questionnaire included ten (10) items soliciting responses on the rating of the level of the respondents’ awareness on research ethics. The rating was done on 3 points scale: high (3), medium (2), and low (1). The data collected were analysed using percentages and mean scores. The criterion mean of 2 was set as the benchmark. It was clear that none of the items met the criterion set as the benchmark except item on knowledge of confidentiality which was high. Their awareness on research ethics generally, awareness on publication practices, collaborative authorship, animal welfare, knowledge of research misconduct, regulations, policies and guidelines that guide research misconduct, putting culture into consideration when carrying research, avoidance of pitfalls in carrying research and awareness that research ethics helps to build public support for research were within the medium range. The need to emphasize quality researches in education cannot be taken for granted. The emerging dynamics of the world necessitated the need to strengthen researches which invariably may attract more research funds to the universities.